2015
DOI: 10.1007/s10620-015-3608-x
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of Non-anesthesia Provider-Administered Propofol (NAAP) Sedation in Advanced Gastrointestinal Endoscopic Procedures: Comparative Meta-Analysis of Pooled Results

Abstract: The safety of NAAP sedation compared favorably with AAP sedation in patients undergoing advanced endoscopic procedures. However, it came at the cost of decreased patient and endoscopist satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
62
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 43 publications
9
62
2
5
Order By: Relevance
“…In addition, since propofol is also used in intensive care patients and with other clinical sedative treatment (9). Propofol has a number of characteristics that make it advantageous as an anesthetic, including taking effect quickly, short metabolic time, easy control of narcosis and slight adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since propofol is also used in intensive care patients and with other clinical sedative treatment (9). Propofol has a number of characteristics that make it advantageous as an anesthetic, including taking effect quickly, short metabolic time, easy control of narcosis and slight adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, the push toward containment of health care costs has brought into question the sustainability of anesthesiologist-administered propofol (AAP) in healthy patients at low risk undergoing routine endoscopic procedures. 12,[16][17][18] In fact, non-anesthesiologistadministered propofol (NAAP) has already been endorsed and widely implemented in several European countries. 17,19 In 2008, Singh and colleagues 7 conducted a systematic review on the safety of NAAP but identified only 1 study comparing NAAP to AAP.…”
mentioning
confidence: 99%
“…In a 2015 comparative metaanalysis, the authors concluded that NAAP compares favourably with AAP for patients undergoing advanced endoscopic procedures. 18 However, the question remains largely unanswered for routine endoscopic procedures. Thus, the purpose of this systematic review was to evaluate whether patient safety and procedure quality are compromised when nonanesthesiologists (i.e., endoscopists) administer propofol in routine upper or lower gastrointestinal endoscopy.…”
mentioning
confidence: 99%
“…Meta-analysis of sedation regimens is usually limited by heterogeneity resulting from varying sedation regimen, the use of additional anesthetics such as morphine derivatives or benzodiazepines, and potential bias in that more complex patients are more likely to be referred to an anesthesiologist [2]. Although this heterogeneity is also present in the study by Goudra et al, its results complement and expand the existing data supporting the general use of AAP-administered sedation in GI endoscopy.…”
mentioning
confidence: 84%
“…In this issue of Digestive Diseases and Sciences, Goudra et al [2] conducted a comparative meta-analysis evaluating respiratory complications of AAP-or NAAP-administered sedation during advanced GI endoscopic procedures. The authors provide data with regard to 3018 advanced GI endoscopic procedures carried out using NAAP-administered sedation and 2374 AAP-administered procedures.…”
mentioning
confidence: 99%